Organ Regeneration Methods and Protocols - basu, joydeep.; basu, joydeep.; Ludlow, John W.; Ludlow, John W. (Methods in Molecular Biology,, 2013)
Tissue engineering and regenerative medicine represents a wide array of cell, biomaterial and cell/biomaterial based approaches focusing on the repair, augmentation, and regeneration of diseases tissues and organs. Organ Regeneration: Methods and Protocols has been assembled in response to the growing interest in organ and tissue regeneration as a means to treat disease. Topics cover methods such as isolation and characterization of cells from selected soft tissues and solid organs, preparation and evaluation of natural and synthetic biomaterial scaffolding, implantation of regenerative constructs within experimental animals, and evaluation of regenerative outcomes by molecular and histological methodologies. Written in the successful Methods in Molecular BiologyTM series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easily accessible, Organ Regeneration: Methods and Protocols serves as a detailed guide to aid newcomers and seasoned veterans in their developmental and experimental work in tissue engineering and regenerative medicine.